Variation in serum levels of Calcium, Phosphorous, Magnesium, Copper and Zinc across productive stages of dairy goats in northwestern Argentina (FAVE Sección Ciencias Veterinarias, 2020)
The aim of this study was to evaluate the serum levels of calcium (Ca), phosphorus (P), magnesium (Mg), copper (Cu), and zinc (Zn) in dairy goats in different productive periods. Twenty Saanen breed goats were selected at different productive stages: prepartum (1 to 2 weeks before partum), postpartum (1 to 2 weeks of lactation), peak of lactation (6 to 8 weeks postpartum) and dry period (15 to 30 days of the final lactation) of a dairy farm in the Valle de Lerma, in the province of Salta. Blood samples were collected and then, Ca, Mg, Cu and Zn levels were measured using atomic absorption spectrophotometry, and P was measured by colorimetric. Hypocalcaemia (7,7±0,2 mg/dL) and hypophosphatemia (3,4±0,4 mg/dL) were found in all production stages. In contrast, Mg levels do not present variation during all the samplings (2.5 ± 0.06 mg / dL). In evaluated micro-minerals, only the serum levels of Zn were lower than those recommended in all the productive periods (53 ± 4 µg / dL). Serum cupper levels were within normal limits (53 ± 4 µg / dL). The obtained results allowed identifying abnormalities in Ca, P and Zn levels during the evaluated productive periods. Information about mineral deficiency in goats is restricted and it is needed to study more about it.
Keywords: mineral deficiency; hypocalcaemia; hypophosphataemia; goats